Preparation of a new polymeric surfactant for emulsion polymerization - Sarac, Ayfer; Senkal, B. Filiz; Yavuz, Erdem; Guersel, Yesim Hepuzer (WILEY-V C H VERLAG GMBH, 2006)
The stability of polymeric dispersions is a property of practical importance and hence, the search for an optimized strategy to equip polymer dispersions with sufficient stability is a matter of continuous research during the last years. The kernel is to reach a sufficient stability, as it is required during polymerization, conditioning, or storage and to allow coagulation or coalescence of particles when it is needed, such as during separation of polymer from latex or during film formation. in this study, the emulsion homopolymerization system containing vinyl acetate, potassium persulfate, new polymeric surfactant, NaHCO3 and water was studied in the classical glass emulsion polymerization reactor. The effects of new polymeric emulsifier on the physicochemical properties of obtained vinyl acetate latex properties were investigated depending on vinyl acetate percentage in homopolymerization.
Keywords: emulsion polymerization; lattices; stabilization; surfactants; vinyl acetate; VINYL-ACETATE; CHAIN-LENGTH; COPOLYMERIZATION; POLYSTYRENE; BEHAVIOR; Polymer Science